Efficacy of acupressure on quality of recovery after surgery: Randomised controlled trial. Issue 8 (August 2019) - Noll, Eric; Shodhan, Shivam; Romeiser, Jamie L.; Madariaga, Maria C.; Page, Christopher; Santangelo, Diane; Guo, Xiaojun; Pryor, Aurora D.; Gan, Tong J.; Bennett-Guerrero, Elliott
Abstract : BACKGROUND: Acupressure therapy is associated with favourable efficacies on postoperative nausea, pain and sleep disturbance, although the quality of the evidence is generally low. No randomised clinical trial has yet assessed the effect of acupressure on postoperative quality of recovery (QoR). OBJECTIVE: The objective was to study acupressure efficacy on patient-reported postoperative recovery. DESIGN: We conducted a single centre, three-group, blind, randomised controlled, pragmatic trial assessing acupressure therapy on the PC6, LI4 and HT7 acupoints. PATIENTS: Postoperative patients expected to stay in hospital at least 2 days after surgery. INTERVENTIONS: In the acupressure group, pressure was applied for 6 min (2 min per acupoint), three times a day after surgery for a maximum of 2 postoperative days during the hospital stay. In the sham group, extremely light touch was applied to the acupoints. The third group did not receive any touch. MAIN OUTCOME MEASURES: The primary outcome was the change in the QoR, using the QoR-15 questionnaire, between postoperative days 1 and 3. Key secondary outcomes included patients' satisfaction, postoperative nausea and vomiting, pain score and opioid (morphine equivalent) consumption. Assessors for the primary and secondary endpoints were blind to the group allocation. RESULTS: Overall, 163 patients were randomised (acupressure n =55, sham n =53, no intervention n =55). The mean (SD) postoperative change in QoR-15 did not differ statistically ( P  = 0.27) between the acupressure, sham and no intervention groups: 15.2 (17.8), 14.2 (21.9), 9.2 (21.7), respectively. Patient satisfaction (on a 0 to 10 scale) was statistically different ( P  = 0.01) among these three groups: 9.1 (1.5), 8.4 (1.6) and 8.2 (2.2), respectively. Changes in pain score and morphine equivalent consumption were not significantly different between the groups. CONCLUSION: Two days of postoperative acupressure therapy (up to six treatments) did not significantly improve patient QoR, postoperative nausea and vomiting, pain score or opioid consumption. Acupressure, however, was associated with improved patient satisfaction. TRIAL REGISTRATION: ClinicalTrials.gov, identifier: NCT02762435.